An indirect criterion for the laminar to turbulent flow transition in shear-driven annular liquid films. (October 2015) - Cioncolini, Andrea; Del Col, Davide; Thome, John R.
Graphical abstract: Highlights: The near wall structure in shear-driven annular liquid films is resolved. The limit between the laminar sublayer and the buffer layer corresponds to ≈9 wall units. The limit between the buffer layer and the turbulent layer corresponds to ≈40 wall units. New laminar to turbulent flow transition criterion for annular liquid films. New prediction method for the average liquid film thickness. Abstract: An indirect method to identify the laminar to turbulent flow transition in shear-driven annular liquid films has been developed and used, together with literature measurements of the velocity profile, to approximately resolve the near wall structure in shear-driven annular liquid films. The limits between the laminar sublayer and the buffer layer and between the buffer layer and the turbulent layer have been found to correspond to about 9 and 40 wall units, respectively, which are higher than the corresponding limits of 5 and 30 wall units typical of single-phase boundary layers, thus indicating a weaker turbulence intensity in shear-driven annular liquid films with respect to single-phase wall-bounded flows. Additionally, a simple laminar to turbulent flow transition criterion and a prediction method for the average liquid film thickness have been developed for evaporation and condensation applications.